Gerakan PBLHS SMA Negeri 1 Bluto: Implementasi Ekonomi Sirkular dan Eco-Entrepreneurship Melalui Teknologi Plastic Crusher - Imam Rofiqi; Very Andrianingsih; Mohammad Firlie Pranata; Evi Dwi Hastri; Moh. Baqir Ainun (Pusat Riset dan Inovasi Nasional, 2026)
Plastic waste management in the school environment remains a fundamental issue that contributes to low levels of student awareness regarding the circular economy and the implementation of the School-Based Environmental Care and Culture Movement (Peduli dan Berbudaya Lingkungan Hidup di Sekolah/PBLHS). This community service program was conducted at SMA Negeri 1 Bluto under the theme of an Eco-Entrepreneurship-Based PBLHS Movement through the implementation of Plastic Crusher technology and Augmented Reality (AR) learning media. The objectives of this program were to enhance students’ understanding, managerial skills, and participation in eco-entrepreneurship-based waste management. The methods employed included socialization, training, mentoring, and the direct application of appropriate technology and interactive learning media. The results indicate significant improvements: students’ understanding of the contribution of the circular economy increased from 20% to 100%, environmental participation rose from 15% to 85%, and students’ managerial skills reached 85%, marked by the establishment of an eco-entrepreneurship group formally authorized through a Principal’s Decree. In addition, one PBLHS implementation roadmap and one digital Business Model Canvas (BMC)-based business model document were developed. In conclusion, this program successfully enhanced students’ capacity in social and managerial aspects through the integration of appropriate technology and digital innovation, thereby supporting the development of a sustainable school culture grounded in circular economy principles and eco-entrepreneurship.